Assessment of Customer Satisfaction Among Electronic Megastores in Colombo City, Sri Lanka - Thelge Sachith, Malintha Peiris (2024)
Observations revealed customer satisfaction of electronic megastores’ customers in Colombo City was decreasing. Studies have identified customer dissatisfaction has become a threat to companies’ survival. Previous research work proved improving service quality led to higher customer satisfaction. It is important for the management of electronic megastores to know what service quality determinants influence customer satisfaction from customers’ perspective and also from the employee’s understanding. Recent observations revealed that there were gaps between employees’ understanding of customers satisfaction and perceived customer satisfaction of service quality which created dissatisfaction among customers. Therefore, a study required to assess the relationship between service quality determinants and customer satisfaction among electronic megastore customers in Colombo City. As there were sufficient evidence proved gaps in service quality affect customer satisfaction, this study attempted identifying relationship between service quality determinants and customer satisfaction and to what extent the gaps between customers perceived importance and employees’ level of understanding to be reduced. Six selected determinants were examined whether both service staff and customers position determinants as a crucial factor for customer satisfaction within electronic megastores. For this purpose, six service quality determinants aligned to SERVQUAL method were tangibility, reliability, responsiveness, assurance, empathy and accessibility’s significant influence on customer satisfaction. As the research instrument, SERVQUAL tested structured questionnaire was distributed and obtained completed 384 responses from visiting customers within six selected electronic megastores by systematic sampling technique. The 384 questionnaires were asked to be completed accurately at the same time of its distribution. SPSS version 21.0 tool was utilized to analyze data using descriptive, mean comparison, simple correlation, ANOVA, coefficients, residuals, independent sample t-test and regression. Findings revealed that customers considered tangibility, reliability, responsiveness, assurance, empathy and accessibility were significantly influencing factors on customer satisfaction. Further findings revealed that there was a significant gap between employees and customers perceived importance of tangibility, reliability, responsiveness, assurance, empathy and accessibility. Subsequently, recommendations were made to improve the service quality determinants and approaches to reduce the gap between employees and customers perceived importance within electronic megastores in Colombo, Sri Lanka.